Optimasi Proses Pengolahan Margarin Krim Skala Pabrik - Henni Rizki Septiana; Dede Robiatul Adawiyah; Nuri Andarwulan (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2015)
Formulation of cream margarine (fat content <80%) has higher water content and more vulnerable to water separation if it is not properly processed. This research is aim to optimize parameter process of cream margarin production by controlling cooling temperature in A unit and C unit rotation in margarine processing unit (MPU), determine minimum throughput of margarine processing unit (MPU), product characterization by conducted chemical and physical analysis and study the effect of direct transport and product’s position in the truck to cream margarine hardness value.. The result showed that the optimum process parameter is SP 6 (AAACAC - 33°C; 21°C; 17°C; 300 rpm; 18°C; 30 rpm which gives expected hardness value. Minimum throughput of margarine processing unit that can achieve 60 gr/cm2 in day 2 is 3000 kg/hour. Product characterization showed that melting point of cream margarin is 36.8°C, water content is 28%, salt content is 2.2%, pH is 4, droplet size is 3.4–4.1μm and solid fat content in 20, 30, 35, and 40°C respectively are 20%, 11%, 7% and 3%. Product that experienced direct transportation give lower hardness value during storage and product’s position in the truck also gives significant impact to hardness value.